Pengaruh Ketepatan Waktu, Akurasi, Kesopanan, Kemudahan, Kenyamanan, dan Atribut Pendukung terhadap Keputusan Menggunakan GrabCar - Muhammad Safriudin; Hadi Jauhari; Lisnini (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
The purpose of this study was to see the effect of Timeliness, Accuracy, Politeness, Ease, Comfort, and Supporting Attributes on Decisions Using GrabCar. The method used is quantitative with data retrieval techniques through questionnaires to tourists who have used GrabCar to amanzi water park attractions numbering 100 respondents. The data analysis using multiple regression analysis. This study shows that Timeliness, Ease, and Comfort have a significant-positive influence on the Decision Using GrabCar as Tourist Transportation. Meanwhile, Accuracy, Politeness, and Supporting Attributes do not have a significant impact. GrabCar's accuracy, politeness, and supporting attributes need to be improved so as to improve decisions using GrabCar.